Users comprehension and behaviour study on android permissions - Awang Abu Bakar, Normi Sham (IIUM Press, 2016)
The Android Market has become the main source of applications (apps) download for Android based devices. The majority of users trust that the apps that they downloaded are safe and trustworthy. However, it is not always the case since a large numbers of apps contain several unnecessary permissions that will potentially provide threats to the users’ privacy and security by stealing their important data, and also offer services that will cost money to the users. The main objective of this paper is to investigate the level of knowledge, understanding and behaviour of the users towards these permissions. The results obtained show that the awareness on these permissions among the users is still low and they need to be cautioned against the potential threats of these permissions to ensure that they can make a well informed decisions whether to install the apps or not.